2020
DOI: 10.1002/adma.202005315
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Tailored Spin Phenomena in a Reduced‐Dimensional Topological Superlattice

Abstract: Hall effect (SHE) and the Rashba-Edelstein effect (REE), [1,2] or vice versa. Emergent topological quantum materials, including topological insulators (TIs), [3-6] Dirac semimetals, [7] and Weyl metals [8-11]-as the key core of quantum material familieshave been compelling due to their order of magnitudes larger charge-to-spin conversion efficiencies compared to those in heavy metals. [12,13] While the spin-to-charge (SCC) efficiencies of most 3D TIs with a single surface state remain moderate, [14,15] the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
3
8
0
Order By: Relevance
“…For sample POST ANN-IL we obtain λ IEE = 0.27 nm, which is in perfect agreement with the value obtained in Au/Co/Au/Sb 2 Te 3 , [4] thus demonstrating the intrinsic role played by Sb 2 Te 3 and its preserved TSS to origin such a large S2C. When compared to other 2 nd class chalcogenide-based TI, [26,[37][38][39][48][49][50][51][52][53][54] the extracted λ IEE is comparable to the highest reported so far.…”
Section: Broadband Fmr Andsupporting
confidence: 88%
See 2 more Smart Citations
“…For sample POST ANN-IL we obtain λ IEE = 0.27 nm, which is in perfect agreement with the value obtained in Au/Co/Au/Sb 2 Te 3 , [4] thus demonstrating the intrinsic role played by Sb 2 Te 3 and its preserved TSS to origin such a large S2C. When compared to other 2 nd class chalcogenide-based TI, [26,[37][38][39][48][49][50][51][52][53][54] the extracted λ IEE is comparable to the highest reported so far.…”
Section: Broadband Fmr Andsupporting
confidence: 88%
“…The AS DEP CEMS-spectrum (Figure 3b) has an overall shape much well-resembling those previously observed at the interface in the 54 Fe/ 57 Fe(1 nm)/Sb 2 Te 3 /SiO 2 /Si heterostructures. [7,10] AS DEP displays a dominant central paramagnetic component, for which the hyperfine parameters do not match those of DOUB-1 in REF.…”
Section: Magnetotransport In Extended Sb 2 Te 3 On Si(111)supporting
confidence: 76%
See 1 more Smart Citation
“…The mutual conversion between the electric and spin current is one of the most important functions of spintronic devices. A logic device known as a magnetoelectric spin–orbit (MESO) device has been proposed that uses spin-to-charge conversion to read data bits. , A topological insulator (TI) hosts a gapless Dirac electronic state with spin-momentum locking on the surface. The Fermi-contoured helical spin polarization of the TI surface has been demonstrated to enable the conversion between spin and charge currents through the Edelstein , and inverse Edelstein effects. In addition, tuning the energy band structure of a TI to eliminate the contribution from the bulk state is crucial to the intrinsic quantum transport of topological surface states. , Recent research on ternary compound TI (Bi 1– x Sb x ) 2 Te 3 has demonstrated that the Dirac surface carriers can become enhanced and tunable compared with the bulk carrier contribution. Spin polarization in the conduction of the (Bi 1– x Sb x ) 2 Te 3 topological surface state has been demonstrated , to be an attractive way to find a material candidate with improved spin-to-charge conversion, but an important question remains unsolved in this case. Does the topological surface state alone produce the maximum efficiency of the spin-to-charge conversion?…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the spin dynamics in GdIG films, we conducted in‐plane FMR measurements. [ 27 ] Here the low‐frequency uniform mode, regarded as the ferromagnetic counterpart, [ 28 ] was triggered by the absorption of radiofrequency/microwave radiation, as illustrated in Figure a. Figure 2b shows the typical FMR spectra recorded as a function of the in‐plane magnetic field ( H ) at various frequencies at 300 K, from which the resonant magnetic field ( H r ) and linewidth (Δ H ) can be obtained.…”
Section: Resultsmentioning
confidence: 99%